2013
DOI: 10.1051/0004-6361/201322078
|View full text |Cite
|
Sign up to set email alerts
|

Astrometric mass ratios for three spectroscopic binaries

Abstract: The orbits of five single-lined spectroscopic binaries have recently been determined. We now use astrometric measurements that were collected with the H satellite to constrain the systems' mass ratios and secondary masses. The barycentric astrometric orbits of three binary systems, HD 140667, HD 158222, and HD 217924, are fully determined and precise estimates of their mass ratios are obtained. Follow-up of these systems with infrared spectroscopy could yield model-independent dynamical masses for all … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…They were fitted with five-parameter models using the orbital parameters obtained from the radial velocities, following the method described in detail by Sahlmann et al (2011). This method has proven to be reliable in detecting astrometric orbital signatures (e.g., Sahlmann et al 2011Sahlmann et al , 2013Díaz et al 2012;Wilson et al 2016). Here we detected no orbital motions.…”
Section: Methodsmentioning
confidence: 99%
“…They were fitted with five-parameter models using the orbital parameters obtained from the radial velocities, following the method described in detail by Sahlmann et al (2011). This method has proven to be reliable in detecting astrometric orbital signatures (e.g., Sahlmann et al 2011Sahlmann et al , 2013Díaz et al 2012;Wilson et al 2016). Here we detected no orbital motions.…”
Section: Methodsmentioning
confidence: 99%
“…Uncertainties in the solution parameters were derived by Monte Carlo simulations, which also propagate the uncertainties in the RV parameters. This method has proven to be reliable in detecting orbital signatures in the H IAD (Sahlmann et al 2011b,a;Díaz et al 2012;Sahlmann & Fekel 2013). Table 4 lists the target names and the basic parameters of the H observations relevant for the astrometric analysis.…”
Section: Analysis Of the Hipparcos Astrometrymentioning
confidence: 99%
“…We search for an orbital signature in Hipparcos IAD using the methodology described in Sahlmann et al (2011b), which has been shown to reliably detect such orbital signatures in Hipparcos IAD (Sahlmann et al 2011b,a;Sahlmann & Fekel 2013). We use the spectroscopic orbital parameters given in Tab.…”
Section: Orbit Analysismentioning
confidence: 99%